Inverted L-Shaped CP Patch Antenna with Corner-Truncated Partial Ground Plane Diagonally Adjoined with Square Branch for L-Band Applications - Phanuphong Boontamchauy; Titipong Lertwiriyaprapa; Chuwong Phongcharoenpanich (My University, 2021)
This research proposes an inverted L-shaped patch antenna with a corner-truncated partial ground plane diagonally adjoined to a square branch for L-band applications. The adjoining square branch was used to perturb linear polarization for circular polarization, and the corner-truncated partial ground plane was utilized to enhance the axial ratio bandwidth (ARBW). Simulations were performed, an antenna prototype was fabricated, and experiments were carried out. The simulation and measured results were in good agreement. The proposed antenna could achieve an ARBW of 77.87% (1.09–2.48 GHz). The novelty of this research lies in the concurrent use of a square branch and a corner-truncated partial ground plane to realize wide ARBW in an L-band, rendering the technology suitable for satellite communication and navigation applications.
Keywords: Ground plane; Square (algebra); Antenna Design and Analysis